The wisdom books : Job, Proverbs, and Ecclesiastes : a translation with commentary - Alter, Robert (New York : W.W. Norton & Co., 2010)
Presents a modern translation of the Books of Job, Proverbs, and Ecclesiastes in the Old Testament, and provides annotations and commentary for each verse.
Job -- Proverbs -- Qohelet (Ecclesiastes)
Includes bibliographical references.
Keywords: Bible. -- Commentaries; Wisdom literature